2021
DOI: 10.1016/j.sjbs.2021.07.083
|View full text |Cite
|
Sign up to set email alerts
|

Control of Fusarium verticillioides on corn with a combination of Bacillus subtilis TM3 formulation and botanical pesticides

Abstract: The aim of this study was to evaluate the effectiveness of the combination of Bacillus subtilis TM3 formulation with botanical pesticides in suppressing Fusarium verticilloides infection in corn. The research was carried out at the Plant Pathology Laboratory and the Experimental Farm of Indonesian Cereals Research Institute (ICERI) from February to November 2019. The research consisted of two stages, namely an in vitro test of antagonists of botanical pesticides ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Our research showed biofertilizers significantly reduced Fusarium and Phytophthora , which was also reported by Sridharan and Suriani 41 , 42 . We also observed that some microbial biofertilizers significantly reduced fungal soil-borne pathogens, even when the cucumber plants were uprooted.…”
Section: Discussionsupporting
confidence: 90%
“…Our research showed biofertilizers significantly reduced Fusarium and Phytophthora , which was also reported by Sridharan and Suriani 41 , 42 . We also observed that some microbial biofertilizers significantly reduced fungal soil-borne pathogens, even when the cucumber plants were uprooted.…”
Section: Discussionsupporting
confidence: 90%
“…Betel extract contains active compounds such as eugenol, chavibetol, and hydroxycavibetol (Naja et al, 2022), each of which has growth-inhibitory properties. In addition to interfering with fungus enzyme activity and metabolic processes and damaging cell membranes, botanical pesticides in betel extract inhibit sporulation (Suriani et al, 2021). Spores are an important reproductive form of fungi in the spread of disease (Odebode et al, 2020).…”
Section: Adiwena Et Al (2024)mentioning
confidence: 99%
“…The current control method for stalk rot in corn still favors synthetic pesticides. However, this requires substantial costs, and chemical residues are harmful to environmental sustainability (Odelade and Babalola 2019;Suriani et al 2021;Kanaan 2021;Mirsam et al 2021a). In addition, the use of pesticides can trigger pathogen gene mutations to become resistant, so these strains are difficult to control (Hobbelen et al 2014).…”
Section: Introductionmentioning
confidence: 99%